Evaluation of indirect diagnostic tests and PBMC expression of innate immune genes in subclinical mastitis in dairy cows - HALLOLLI, AVINASH C; SHARMA, DEEPAK; MANIMARAN, AYYASAMY; KUMARESAN, ARUMUGAM; SIVARAM, MUNIANDY; BAGATH, MADIAJAGAN; PRAKASH, M ARUL; JEYAKUMAR, SAKTHIVEL; RAJENDRAN, DURAISAMY (The Indian Journal of Animal Sciences, 2021)
The aim of this study was to estimate the prevalence of subclinical mastitis (SCM), its innate immunity and to compare the efficacy of indirect diagnostic tests [California mastitis test (CMT), differential electrical conductivity (DEC), absolute EC, enzyme based color detection method (Tanucheck kit) and brothymol blue strip (BTB) tests] to milk somatic cell count (SCC) method using 200×103 cells/ml as a cut off value in Deoni (N=27) and HF crossbred (N=32) cows. Cumulative prevalence of SCM was 38% and 63% in Deoni and HF crossbred cows, respectively on milk SCC basis (N=215). Breed, udder health status and its interaction had significant effect on SCC level. The overall sensitivity and specificity of above indirect tests were 38 and 99%; 52 and 72%; 52 and 69%; 76 and 31%, and 1 and 100%, respectively. mRNA expression of serum amyloid A (SAA), IL-1β and TNF- α genes were significantly up-regulated while, TNF-α gene was significantly down-regulated in PBMC of SCM affected HF crossbred and Deoni cows, respectively. It is concluded that, DEC is more suitable indirect method to detect SCM and mRNA expression of SAA and TNF-α was strongly related to SCM in HF crossbred and Deoni cows, respectively.